Comparison of four methods for the biofunctionalization of gold nanorods by the introduction of sulfhydryl groups to antibodies - Wang, Xuefeng; Mei, Zhong; Wang, Yanyan; Tang, Liang (Beilstein Journal of Nanotechnology, 2017)
Introducing sulfhydryl groups to biomolecules to functionalize gold nanorods (GNRs) is an attractive method that involves the creation of a strong Au–S bond. Previously, we developed a facile method to functionalize GNR surfaces by thiolating antibodies using Traut’s reagent. In the current study, we evaluated several methods for the introduction of thiol groups onto the surface of GNRs by using Traut’s reagent, dithiotreitol (DTT), dithiolaromatic PEG6-CONHNH2, and thiol-polyethylene glycolamine (SH-PEG-NH2) combined with EDC reaction. We showed that the four above-mentioned thiolation methods can efficiently functionalize GNRs and simplify the functionalization procedures. The formed GNR-bioconjugates showed superior stability without compromising the biological activity. The GNR nanochip prepared with these four thiolated antibodies can detect human IgG targets with specificity. However, SH-PEG-NH2 combined with EDC reaction may affect the amount of functionalized GNRs because of the efficiency of thiol moiety linkage to antibodies, thereby affecting the sensitivity of the GNR sensor. The introduction of a thiol group to antibodies by using Traut’s reagent, DTT, and PEG6-CONHNH2 allowed for direct immobilization onto the GNR surface, improved the efficacy of functionalized GNRs, and increased the sensitivity in response to target detection as a biosensor. Given that PEG6-CONHNH2 modification requires glycosylated biomolecules, Traut’s reagent and DTT thiolation are recommended as universal applications of GNR biofunctionalization and can be easily extended to other sensing applications based on other gold nanostructures or new biomolecules.
Keywords: biofunctionalization; biosensing; four methods; gold nanorod; introduction of sulfhydryl groups

(untitled) - Azimzadeh, M.; Rahaie, M.; Nasirizadeh, N.; Ashtari, K.; Naderi-Manesh, H. (Biosens. Bioelectron., 2016)

(untitled) - Chen, S.; Zhao, Q.; Zhang, L.; Wang, L.; Zeng, Y.; Huang, H. (Sens. Actuators, B, 2015)

(untitled) - Xu, X.; Liu, X.; Li, Y.; Ying, Y. (Biosens. Bioelectron., 2013)

(untitled) - Wang, B.-K.; Yu, X.-F.; Wang, J.-H.; Li, Z.-B.; Li, P.-H.; Wang, H.; Song, L.; Chu, P. K.; Li, C. (Biomaterials, 2016)

(untitled) - Li, Z.; Huang, H.; Tang, S.; Li, Y.; Yu, X.-F.; Wang, H.; Li, P.; Sun, Z.; Zhang, H.; Liu, C.; Chu, P. K. (Biomaterials, 2016)

(untitled) - Arunkumar, P.; Raju, B.; Vasantharaja, R.; Vijayaraghavan, S.; Preetham Kumar, B.; Jeganathan, K.; Premkumar, K. (Nanomedicine, 2015)

(untitled) - Fournelle, M.; Bost, W.; Tarner, I. H.; Lehmberg, T.; Weiß, E.; Lemor, R.; Dinser, R. (Nanomedicine, 2012)

(untitled) - Naz, G.; Othaman, Z.; Shamsuddin, M.; Krishna Ghoshal, S. (Mater. Lett., 2016)

(untitled) - Wang, F.; Shen, Y.; Zhang, W.; Li, M.; Wang, Y.; Zhou, D.; Guo, S. (J. Controlled Release, 2014)

(untitled) - Cao, J.; Sun, T.; Grattan, K. T. V. (Sens. Actuators, B, 2014)

(untitled) - Wijaya, E.; Lenaerts, C.; Maricot, S.; Hastanin, J.; Habraken, S.; Vilcot, J.-P.; Boukherroub, R.; Szunerits, S. (Curr. Opin. Solid State Mater. Sci., 2011)

(untitled) - Muddineti, O. S.; Ghosh, B.; Biswas, S. (Int. J. Pharm., 2015)

(untitled) - Monem, A. S.; Elbialy, N.; Mohamed, N. (Int. J. Pharm., 2014)

(untitled) - Huang, X.; Neretina, S.; El-Sayed, M. A. (Adv. Mater., 2009)

(untitled) - Li, X.; Kao, F.-J.; Chuang, C.-C.; He, S. (Opt. Express, 2010)

(untitled) - Shah, M.; Badwaik, V. D.; Dakshinamurthy, R. (J. Nanosci. Nanotechnol., 2014)

(untitled) - Wang, X.; Mei, Z.; Wang, Y.; Tang, L. (Talanta, 2015)

(untitled) - Wang, Y.; Tang, L. (Biosens. Bioelectron., 2015)

(untitled) - Ji, T.; Muenker, M. C.; Papineni, R. V. L.; Harder, J. W.; Vizard, D. L.; McLaughlin, W. E. (Bioconjugate Chem., 2010)

(untitled) - Packard, B.; Edidin, M.; Komoriya, A. (Biochemistry, 1986)

(untitled) - Pathak, S.; Davidson, M. C.; Silva, G. A. (Nano Lett., 2007)

(untitled) - Kumar, S.; Aaron, J.; Sokolov, K. (Nat. Protoc., 2008)

(untitled) - Joshi, P. P.; Yoon, S. J.; Hardin, W. G.; Emelianov, S.; Sokolov, K. V. (Bioconjugate Chem., 2013)

(untitled) - Tinguely, J.-C.; Charron, G.; Lau-Truong, S.; Hohenau, A.; Grand, J.; Félidj, N.; Aubard, J.; Krenn, J. R. (J. Colloid Interface Sci., 2013)

(untitled) - Huang, X.; Peng, X.; Wang, Y.; Wang, Y.; Shin, D. M.; El-Sayed, M. A.; Nie, S. (ACS Nano, 2010)

(untitled) - Hume, P. S.; He, J.; Haskins, K.; Anseth, K. S. (Biomaterials, 2012)

(untitled) - Xue, C.; Zhao, H.; liu, H.; Chen, Y.; Wang, B.; Zhang, Q.; Wu, X. (Sens. Actuators, B, 2011)

(untitled) - Weber, C.; Reiss, S.; Langer, K. (Int. J. Pharm., 2000)

(untitled) - Sau, T. K.; Murphy, C. J. (Langmuir, 2004)

(untitled) - Ye, X.; Zheng, C.; Chen, J.; Gao, Y.; Murray, C. B. (Nano Lett., 2013)

(untitled) - Wang, Y.; Tang, L. (Anal. Chim. Acta, 2013)